Revitalization and Adaptive Re-use in Cappadocia: A Taxonomy of Creative Design Solutions for Uchisar Boutique Hotels - Suzan Girginkaya Akdağ; Berna Sayar (Alanya Hamdullah Emin Paşa Üniversitesi, 2020)
The